(untitled) (Damascus University Journal for legal sciences, 2026)
Business is an essential engine for economic growth in countries, whether developing or developed, due to the role it plays in economic and social terms. It contributes to increasing the national income, providing many job opportunities, and reducing the spread of unemployment. However, these projects, regardless of their size or the nature of their activities, may be exposed to some financial crises while carrying out their work, which may lead to disruption of their financial position and stop paying their debts on the specified dates, which leads to their bankruptcy and exit from the commercial market, and given the importance of these commercial projects; Many countries in the world have organized a mechanism aimed at addressing the financial or administrative turmoil that may befall them during the conduct of their activities, and this mechanism is restructuring.